Segregated Expression of ENaC Subunits in Taste Cells. (1st February 2020) - Lossow, Kristina; Hermans-Borgmeyer, Irm; Meyerhof, Wolfgang; Behrens, Maik
Abstract: Salt taste is one of the 5 basic taste qualities. Depending on the concentration, table salt is perceived either as appetitive or aversive, suggesting the contribution of several mechanisms to salt taste, distinguishable by their sensitivity to the epithelial sodium channel (ENaC) blocker amiloride. A taste-specific knockout of the α-subunit of the ENaC revealed the relevance of this polypeptide for low-salt transduction, whereas the response to other taste qualities remained normal. The fully functional ENaC is composed of α-, β-, and γ-subunits. In taste tissue, however, the precise constitution of the channel and the cell population responsible for detecting table salt remain uncertain. In order to examine the cells and subunits building the ENaC, we generated mice carrying modified alleles allowing the synthesis of green and red fluorescent proteins in cells expressing the α- and β-subunit, respectively. Fluorescence signals were detected in all types of taste papillae and in taste buds of the soft palate and naso-incisor duct. However, the lingual expression patterns of the reporters differed depending on tongue topography. Additionally, immunohistochemistry for the γ-subunit of the ENaC revealed a lack of overlap between all potential subunits. The data suggest that amiloride-sensitive recognition of table salt is unlikely to depend on the classical ENaCs formed by α-, β-, and γ-subunits and ask for a careful investigation of the channel composition.